A work in progress: integrating markets for goods, labor, and capital in the east African community - Alper, Emre C.; Chen, Wenjie; Dridi, Jemma; Joly, Hervé; Yang, Fan; International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2017)
This paper assesses the extent of economic and financial integration among the East African Community (EAC) along a number of dimensions and, where possible, whether integration has increased in the wake of the major regional integration policy milestones.
1. Analysis of merchandise trade integration in the EAC Evolution of tariffs and imports of EAC countries since the implementation of the CU -- Evolution of intra-EAC trade as a share of total trade -- Trade integration in the EAC compared with other regions -- 2. Labor migration and remittances in the EAC Progress in eliminating legislative restrictions to the movement of workers in the EAC -- Recent migration and remittances trends in the EAC -- 3. Financial integration in the EAC Progress in eliminating legislative restrictions in EAC capital markets -- Openness to capital flows in the EAC: A comparative perspective -- An empirical assessment of the CIP condition in Kenya, Tanzania, and Uganda -- An assessment of financial market convergence in the EAC -- Appendices
Includes bibliographical references (P. 33-35)
Keywords: International economics; ECONOMIC DEVELOPMENT; ECONOMIC INTEGRATION; AFRICA; EAST AFRICA